1991
DOI: 10.3109/10731199109117853
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of Plasticizers from and Surface Characterization of PVC Blood Platelet Bags

Abstract: The leaching of phthalate plasticizers from four types of blood platelet bags was investigated. The anticoagulant solutions used in the blood collection bags had pH values of 5.64 +/- .04 and contained no detectable amounts of phthalates. Platelet bag materials from each bag were soaked in normal salines for up to 5 days. The salines were tested for the leached phthalates from the bags but none could be found. However, di-(2-ethylhexyl) phthalate (DEHP) leached out of the PL-146 and Terumo bags into bovine cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…55 Studies have systematically found significantly less or no leaching of TETM compared with DEHP from medical devices such as hemodialysis tubing and blood platelet bags into human and calf serum, respectively. 6973 The most common applications of TETM are in medical products, specifically blood bags and infusion sets, packing, cables, floor and wall coverings. 14,47 …”
Section: Dehp-free Plasticizersmentioning
confidence: 99%
“…55 Studies have systematically found significantly less or no leaching of TETM compared with DEHP from medical devices such as hemodialysis tubing and blood platelet bags into human and calf serum, respectively. 6973 The most common applications of TETM are in medical products, specifically blood bags and infusion sets, packing, cables, floor and wall coverings. 14,47 …”
Section: Dehp-free Plasticizersmentioning
confidence: 99%
“…This could result in under-dose, and a greater amount of drug to compensate for the adsorption loss may be required. Although the significance of the inner surface morphologies of IV bags is not certain, different brands of IV bags can differ very significantly [15]. Loss of Factor VIII (FVIII) activity in IV infusion systems was reported to be caused by FVIII binding to plastic surfaces [16,17]; the two reports differ in that the former reported initial drop in recovery, while the latter reported a continuous loss of activity.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous reports on the leachables, such as metals, DEHP, cyclohexanone, and other organic and acidic compounds, found in the solution of PVC bags [15,[18][19][20][21][22]. The leachables have the potential to interact with and alter the drug to be administered [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the same membranes were immersed in water for a 7-day period and each phthalic acid ester was then measured for absorbance before and after which gave an indication of the rate of biocidal activity. Each phthalate had the following IR-bands monitored ϑC O stretching (1727 cm −1 ), CH 2 CH 3 vibration (1291 cm −1 , 1128 cm −1 ), C-Cl (1076 cm −1 , and 976 cm −1 ) which relate to phthalic acid esters in the PVC matrix [38]. DEHP (29.45%) leached significantly lower than the other plasticizers.…”
Section: Availability Of Plasticizermentioning
confidence: 99%